The influence of bamboo fiber (gigantochloa apus) positioning on the flexural strength of heat-cured acrylic resin: an experimental research - Nawawi, Azkya Patria; Endro, Hartanto; Hamumpuni, Tarish; Assoratgoon, Itt (Universitas Padjadjaran, 2025)
Introduction: Acrylic resin is prone to fracture. Apus bamboo fiber (Gigantochloa apus), a natural fiber, is anticipated to enhance the flexural strength of acrylic resin. The fiber's position within the acrylic resin matrix is hypothesized to influence its effectiveness in improving flexural strength. The objective of this study was to investigate the impact of incorporating apus bamboo fibers, based on their position, on the flexural strength of heat-cured acrylic resin plates. Methods: This study employed a laboratory experimental design with a post-test only control group. Twelve rectangular heat-cured acrylic resin plates, measuring 65 mm × 10 mm × 2.5 mm, were prepared in accordance with ISO 178:2019 and were thoroughly polished. The samples were divided into four groups, including three groups with the addition of apus bamboo fiber at a concentration of 1.6%, positioned at the upper, middle, and lower sections and one negative control group consisting of heat-cured acrylic resin plate without the addition of apus bamboo fiber. The samples underwent a three-point bending test using a Universal Testing Machine (UTM). Data analysis was conducted using a one-way ANOVA and an independent t-test. Results: The average flexural strength was 89.34 MPa in the negative control group, 69.35 MPa in the upper fiber group, 82.54 MPa in the middle fiber group, and 106.98 MPa in the lower fiber group. Statistical analysis indicated that the position of apus bamboo fibers significantly affected flexural strength (p<0.05). Conclusion: It can be concluded that the position of apus bamboo fibers influences the flexural strength of heat-cured acrylic resin. Apus bamboo fibers placed in the lower position, corresponding to the anatomical base of the denture, exhibited the highest flexural strength among all groups.